HR-Finance Synergy for MSMEs: Peran Manajemen SDM dan Keuangan untuk Penguatan Daya Saing UMKM Lokal di Kota Makassar - Sri Prilmayanti Awaluddin; Taufik Thahir; Mariati M; Asri Nur Muin (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to analyze the role of human resource management and financial management in strengthening the competitiveness of local MSMEs in Makassar City through the HR-Finance Synergy approach. The background of this study is based on the condition of MSMEs that have proximity to the market and business flexibility, but are not fully supported by integrated HR and financial management. The study uses a quantitative explanatory approach with a survey method of 150 MSME actors in Makassar City. Data were analyzed using multiple linear regression and interaction models with the help of SPSS. The results show that human resource management has a positive effect on MSME competitiveness through the division of tasks, skill improvement, work motivation, and service consistency. Financial management also has a positive and relatively more dominant effect, especially through financial recording, cash flow control, separation of personal and business finances, and capital planning. The main findings of this study show a significant interaction between HR management and financial management, which indicates that MSME competitiveness increases more strongly when both functions are managed in an integrated manner. This research contributes by emphasizing the importance of the HR-Finance Synergy approach in strengthening the competitiveness of MSMEs and provides implications for designing integrative and sustainable business mentoring programs